Critical purviews where Information and Communication Technology (ICT) can promote sustaineble development in Nigeria - Mohammed Ibrahim, Adamkolo; Hassan, Md. Salleh (Global Network of Communication Scholars, 2014)
Information and communication technology (ICT) has become the buzz word in academia, government, business, economy and many other social purviews of human society, especially in the areas of sustainable development. From a mere acronym, ICT has over the last decade metamorphosed into the driving force behind many monumental changes and innovative development in the world. The author reviewed e-journal articles, chapters from e-books and other relevant literature that critically examined ICT and its wider applications in the realms of making life better for the majority of the people, particularly the indigent and information have-nots. The paper critically discusses and analyses some of the key areas where a successful application of ICT can effectively engender the much needed sustainable development in society, focusing on Nigeria. Moreover, the paper outlines, inter-alia, agriculture, culture, economy, education, governance and tourism as paramount realms in which the proper application of ICT can help in the management of natural, human and capital resources for effective utilisation by the present generation without jeopardising the ability of future generations to benefit from them. The paper concludes that for ICT to serve as a catalyst for sustainable development, the following facts should be taken into consideration and adjustments made to accommodate them: ICT is a long-range investment (outcomes may be delayed); and, for natural resources to be sustainably harnessed, human resources ought to be adequately mobilised to appropriately manipulate the capital resources for better results.